The use of peer-correction strategies to improve speaking skills when learning english as a foreign language - Luna López, Tania (2021)
Nowadays it is common, in educational contexts, to hear about the term applied linguistics which is a field of linguistics that focuses on the scientific study of human natural language with an important impact on fields as diverse as education, anthropology, sociology, language teaching, cognitive psychology, philosophy, computer science, neuroscience, and artificial intelligence, among others Akmajian (2010, p. 5). The use of applied linguistics to the teaching of foreign languages has become popular nowadays